Effects of microstructure shape parameters on water removal in a PEMFC lotus-like flow channel. (15th January 2022) - Xie, Xuan; Yin, Bifeng; Xu, Sheng; Jia, Hekun; Dong, Fei; Chen, Xin
Abstract: To improve the drag reduction performances of the proton exchange membrane fuel cell (PEMFC), a three dimensional numerical investigation about the water removal in a lotus-like PEMFC flow channel is carried out. The effects of the microstructure shape parameters (height, radius and spacing) are investigated. The investigation revealed that the liquid water can be effectively removed by the lotus-like flow channel from the channel wall surface. The appropriate height of lotus-like channel can effectively reduce the water coverage ratio on the top wall of the lotus-like flow channel. As height increases, the average drag reduction ratio increases firstly and decreases finally. When the radiuses are 25 μm and 50 μm, the average drag reduction ratios of these cases are higher than those of the other cases obviously. The spacing of the lotus-like channel has a few effects on the water removal and water coverage ratio. The lotus-like flow channel with the height of 50 μm, the radius of 50 μm and the spacing of 150 μm has a high drag reduction and anti-corrosion performance. The work in this study provides a new choice for the flow channel and has certain guiding significance for the design of the flow channel for anti-corrosion and drag reduction. Highlights: A three-dimensional numerical simulation of water behavior was carried out. The lotus-like flow channel can accelerate the water removal. As the height increases, the average drag reduction ratio increases. The radius of the microstructure has influence on the droplet flow velocity. The spacing has an inapparent effect on droplet movement.